A new species and records of Anacroneuria (Plecoptera: Perlidae) from the Ecological Station, Wenceslau Guimaraes, State of Bahia, Brazil - De Almeida, Lucas Henrique [UNESP]; Duarte, Tacio (Magnolia Press, 2017)
We studied specimens of the perlid genus Anacroneuria collected at the Ecological Station, Wenceslau Guimaraes, State of Bahia, Brazil. A list of Anacroneuria species is provided including a description of a new species, A. patioba n. sp., and a new record is given for A. paprockii Novaes & Bispo, 2014.
Keywords: Aquatic insects; Stoneflies; Neotropical Region; Atlantic forest; Streams